PENGEMBANGAN MODEL PROJECT-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BAHASA INGGRIS SISWA PONPES MODERN DI MALANG RAYA - Suhartatik, Suhartatik; Adi, Adi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2014)
English is taught in Modern Islamic Boarding SchoolÂ as one ofÂ language competences must be mastered by the studentsÂ beside Arabic. The teachers findÂ difficulties to implementÂ learning models that make the students to be activeÂ andÂ the students need others learning variation.Â Research and Development (R D) design is used in thisÂ researchÂ that aimÂ to produce the development of â€œProject Based-Learning Modelâ€ plus VCD to improve the Students' English Ability of Modern Islamic Boarding School at Malang Area. The model of development is adopted byÂ Borg and Gall ModelÂ starting from collecting information,Â development of initial product, 1st expert validation, 1stÂ product revision, 2nd expert validation, 2nd product revision, tryout, and final product. The Expertsâ€™ English Material validation conclude that formulation of learning objective, content, material selection for development of â€œProject Based-Learning Modelâ€ have got category ofÂ Excellent. The validation of the Expert of MediaÂ conclude that final product of VCD have been appropriatedÂ with the aspectsÂ ofÂ learning media that are feasible to be applied.